Imaging plasma membrane phase behaviour in live cells using a thiophene-based molecular rotor. - Dent, M; López-Duarte, I; Dickson, C; Chairatana, P; Anderson, H; Gould, I; Wylie, D; Vyšniauskas, A; Brooks, N; Kuimova, M (Royal Society of Chemistry, 2016)
Molecular rotors have emerged as versatile probes of microscopic viscosity in lipid bilayers, although it has proved difficult to find probes that stain both phases equally in phase-separated bilayers. Here, we investigate the use of a membrane-targeting viscosity-sensitive fluorophore based on a thiophene moiety with equal affinity for ordered and disordered lipid domains, to probe ordering and viscosity within artificial lipid bilayers and live cell plasma membranes.